Activities of membarong on Dadak Merak mask dancers of Reog Ponorogo (Indonesia) and the effects on their teeth - Hayyumu Farina Nurhalizah (Indonesian Journal of Social Sciences, 2021)
Reog Ponorogo is an art that uses the Dadak Merak mask which is used by the dancer by biting on a wooden stick inside or commonly called cokotan. The Dadak Merak mask dancer is called pembarong, while the activity of playing the Dadak Merak mask is called membarong or mbarong. A pembarong may do a range of tricks, including kayang, gulungan, lifting the stacked Dadak Merak mask, and lifting the Dadak Merak mask while mounted on someone, all while the mask's weight exceeds 50 kg to 80 kg.  The researchers wanted to know if mbarong action on the Dadak Merak Reog Ponorogo dancer produces tooth wear and how many degrees of wear there are on the dancer's teeth. Cross-tabulation analysis is the data analysis technique employed in this paper. This study included 20 pembarong respondents, ranging in age from 15 to 50 years old. The conclusions of this study show that mbarong exercise produced tooth wear in the dancers, with the most severe wear occurring in the first and second molars. The fulcrum of the Dadak Merak mask load on those teeth causes wear in the first and second molar teeth.